Hypertrophic cardiomyopathy due to sarcomeric gene mutations is characterized by impaired energy metabolism irrespective of the degree of hypertrophy. - Crilley, J; Boehm, E; Blair, E; Rajagopalan, B; Blamire, A; Styles, P; McKenna, W; Ostman-Smith, I; Clarke, K; Watkins, H (2003)
OBJECTIVES: We investigated cardiac energetics in subjects with mutations in three different familial hypertrophic cardiomyopathy (HCM) disease genes, some of whom were nonpenetrant carriers without hypertrophy, using phosphorus-31 magnetic resonance spectroscopy. BACKGROUND: Familial hypertrophic cardiomyopathy is caused by mutations in sarcomeric protein genes. The mechanism by which these mutant proteins cause disease is uncertain. A defect of myocyte contractility had been proposed, but in vitro studies of force generation have subsequently shown opposing results in different classes of mutation. An alternative hypothesis of "energy compromise" resulting from inefficient utilization of adenosine triphosphate (ATP) has been suggested, but in vivo data in humans with genotyped HCM are lacking. METHODS: The cardiac phosphocreatine (PCr) to ATP ratio was determined at rest in 31 patients harboring mutations in the genes for either beta-myosin heavy chain, cardiac troponin T, or myosin-binding protein C, and in 24 controls. Transthoracic echocardiography was used to measure left ventricular (LV) dimensions and maximal wall thickness. RESULTS: The PCr/ATP was reduced in the HCM subjects by 30% relative to controls (1.70 +/- 0.43 vs. 2.44 +/- 0.30; p < 0.001), and the reduction was of a similar magnitude in all three disease-gene groups. The PCr/ATP was equally reduced in subjects with (n = 24) and without (n = 7) LV hypertrophy. CONCLUSIONS: Our data provide evidence of a bioenergetic deficit in genotype-confirmed HCM, which is present to a similar degree in three disease-gene groups. The presence of energetic abnormalities, even in those without hypertrophy, supports a proposed link between altered cardiac energetics and development of the disease phenotype.